2017
DOI: 10.1515/msd-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Antibacterial Activity of Hibiscus sabdariffa Extracts

Abstract: This paper focuses on studying the antibacterial effect ofHibiscus sabdariffaextracts, a plant known in traditional medicine for its beneficial effects on the body.Hibiscus sabdariffaextracts were done in pure water, 50% ethyl alcohol, and 96% ethyl alcohol; the concentrations used to determine antibacterial activity were 1:1, 1:5, 1:10, 1:25, 1:50, noted cu 1, 2, 3, 4, 5. The antibacterial effect of the extracts was tested using the impregnated disk-diffusion method on bacteriaEscherichia coliATCC 25922,Salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…each at 200 mg/mL. Results similar to those obtained from this study were also seen in that of Panaitescu and Lengyel [24] in which H. sabdariffa extracts were found to inhibit growth in E. coli, S. typhi, K. pneumonia and S. aureus used in the study. Inhibitory concentrations were 4, 10, 20 and 100% respectively, while inhibitory zone diameters ranged within 0.1 and 5.0 mm.…”
Section: Susceptibility Of the Test Organisms To Zobo Leaf (H Sabdariffa)supporting
confidence: 88%
See 1 more Smart Citation
“…each at 200 mg/mL. Results similar to those obtained from this study were also seen in that of Panaitescu and Lengyel [24] in which H. sabdariffa extracts were found to inhibit growth in E. coli, S. typhi, K. pneumonia and S. aureus used in the study. Inhibitory concentrations were 4, 10, 20 and 100% respectively, while inhibitory zone diameters ranged within 0.1 and 5.0 mm.…”
Section: Susceptibility Of the Test Organisms To Zobo Leaf (H Sabdariffa)supporting
confidence: 88%
“…The result also showed that out of the four concentrations of the dry hot aqueous extract, only the 0.25 µg/mL concentration was able to show 14.2±0.0 mm inhibition on S. aureus, while the concentrations of 0.25 µg/mL and 0.125 µg/mL were the only two concentrations of the dry alcohol that showed levels of sensitivity with zone diameters of 29.3±1.0 and 25.2±0.0, respectively. The antimicrobial activities of zobo leaf extracts have been reported by previous studies [22,23,24,25,26,27]. In the study of Salem et al [22], it was shown to inhibit S. aureus, K. pneumoniae and E. coli, at minimum concentrations ranging from 0.30 to1.30±0.2 mg/mL for the three organisms.…”
Section: Susceptibility Of the Test Organisms To Zobo Leaf (H Sabdariffa)supporting
confidence: 52%
“…Experimental evaluation of their pharmacological use can provide evidence based alternative therapies for herbal drug and/or discovery of novel drug targets. Hibiscus is often taken as a beverage in many countries owing to its medicinal properties [9,10,20]. In this study, we provide evidence for the anti-microbial property of Hs extract with special emphasis on its effect on C. albicans growth and biofilm formation.…”
Section: Resultsmentioning
confidence: 86%
“…The sensitivity against the tested bacteria differed, with B. atrophaeus being the most sensitive with inhibition zone of approx 1.5 cm in DMSO based extract and 1.2 cm in aqueous extract, while the least sensitive was E. coli with a zone of approximately 1.0 cm in both the extracts. Previous studies have shown the anti-bacterial effect of Hs calyces extract using different solvents such as methanol or ethanol [10,25].…”
Section: Anti-microbial Effect Of Hs Crude Extractsmentioning
confidence: 99%
See 1 more Smart Citation